2011
DOI: 10.1055/s-0031-1291436
|View full text |Cite
|
Sign up to set email alerts
|

Colon tumors and colonoscopy

Abstract: A large number of abstracts dealing with colonoscopy were presented at Digestive Disease Week (DDW; 7-10 May 2011; Chicago, Illinois, USA). Topics included: new techniques in colonoscopy, recent innovations in endoscopic ultrasonography (EUS), prevention of postpolypectomy bleeding, Raman spectroscopy, bowel preparation during colonoscopy, risk factors for high grade dysplasia (HGD) in colonic adenoma, recent advances in endoscopic treatment of colorectal cancer (CRC), and follow-up of HGD and CRC after endosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…117 In recent years, a series of studies have demonstrated that it is feasible and safe to use the endoscopic Raman systems for accurate early qualitative diagnosis and real-time tumor margin identification of gastric, 118 esophageal, 119 and colorectal cancers. 120 Either surgical navigation or endoscopic systems play an extremely important role in the diagnosis and treatment of PC. Hence, it is reasonable to assume that combining SERS technology with intraoperative navigation systems or SERS technology with endoscopic technology to improve the early diagnosis and survival rates of PC is feasible shortly and is one of the research directions that deserves our focused attention.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…117 In recent years, a series of studies have demonstrated that it is feasible and safe to use the endoscopic Raman systems for accurate early qualitative diagnosis and real-time tumor margin identification of gastric, 118 esophageal, 119 and colorectal cancers. 120 Either surgical navigation or endoscopic systems play an extremely important role in the diagnosis and treatment of PC. Hence, it is reasonable to assume that combining SERS technology with intraoperative navigation systems or SERS technology with endoscopic technology to improve the early diagnosis and survival rates of PC is feasible shortly and is one of the research directions that deserves our focused attention.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…The strategy was subsequently demonstrated in an animal glioma precision resection experiment 117 . In recent years, a series of studies have demonstrated that it is feasible and safe to use the endoscopic Raman systems for accurate early qualitative diagnosis and real‐time tumor margin identification of gastric, 118 esophageal, 119 and colorectal cancers 120 . Either surgical navigation or endoscopic systems play an extremely important role in the diagnosis and treatment of PC.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…Evaluation of the circumferential resection margin is important [ 98 ]. MRI Pathological diagnosis is the gold standard for cancer diagnosis [ 108 ]. Invasive procedure; complications occurred such as hemorrhage, perforation The main local changes of intestinal mucosa in early colorectal cancer were observed by gross morphology.…”
Section: Introductionmentioning
confidence: 99%
“… Invasive procedure; complications occurred such as hemorrhage, perforation The main local changes of intestinal mucosa in early colorectal cancer were observed by gross morphology. The intestinal wall tissue was taken out for pathological examination to determine whether there was disease [ 108 , 109 ]. e-colonoscopy It is used to diagnose small primary tumours and metastases less than 3 mm in diameter with high spatial resolution and high temporal resolution.…”
Section: Introductionmentioning
confidence: 99%